(untitled) (Hekima Review, 2015)
The 21st Century has seen growing interest in the protection of Mother Earth which is considered our common home as human beings. This interest comes as a result of massive environmental degradation by man. Man stands at the centre of creation for he enjoys the privilege of being created in the image and likeness of God. He was given the divine mandate to be fertile and multiply; to fill and subdue the earth. But is a man entitled to see himself as lord and master with power to plunder the earth at will? Is man culpable for destroying the environment or the blame falls on the creator who endowed him with free will? I seek to answer these questions in light of St. Augustine’s concept of human freedom, attributing the problem of environmental degradation to sin, which consequently darkened and weakened the human will to choose the good.